Broadband adoption in Pakistan. (6th September 2007) - Khoumbati, Khalil; Dwivedi, Yogesh Kumar; Lal, Banita; Chen, Hsin
The aim of this study is to provide a context for understanding the factors affecting the adoption of broadband internet in a developing country context, in this instance, Pakistan. In order to achieve the stated aim, this study identified and examined various attitudinal, normative and control factors to provide insights into broadband adoption. The data on these variables was collected using a survey approach. A self-administered questionnaire was sent between October and December 2006 to 275 consumers, with a total of 237 responses obtained from the respondents. The findings of this paper suggest that primary influence, facilitating conditions resources, cost and perceived ease of use are significant factors for explaining behavioural intentions to adopt broadband in Pakistan. The paper also outlines the theoretical contributions, implications for practice and limitations of this research.